Uji Kepekaan Bakteri Escherichia Coli Hasil Isolasi Dari Urin Pasien Rumah Sakit Dr. Sardjito Terhadap Antibiotik Golongan P-Laktam - Sri Harnanik; Sri Mulyaningsih; Asih Triastuti (Universitas Islam Indonesia, 2005)
Uncontrolled use of antibiotic caused the emergence of bacteria strain resistant toward of antibiotic. The sensitivity assay of E. coli toward p-lactam antibiotic has been done. The sensitivity assay was started with isolated bacteria from patients urine at Dr. Sardjito hospital followed by count total of colony/number of germ which growth and identified the bacteria. The Kirby Bauer method was performed. Antibiotic impregnated disk (ampicillin 30 ng, sulbactam/ampicillin 20 ng, cefotaxim 30 ng, ceftazidime 30 jig, ceftriaxon 30 ng, cefpirom 30 ng, cefepim 30 ng and imipenem 10 ng) were placed on agar plate previously streaked with suspension of E. coli (1.10 CFU/ml). The plates were incubated for 18-24 hours at 37° C. The diameters of the zone inhibition were measured, and compared to standar interpretive zone sizes. The result of the study showed that all of E. coli resistant toward antibiotic ampicillin; 65% resistant toward antibiotic sulbactam/ampicillin; 50% still sensitive toward antibiotic third cefalosporin generation that is cefotaxim, ceftazidime, ceftriaxon; more than 50% sensitive toward fourth cefalosporin generation like cefepim, cefpirom and all of pathogen bacteria E. coli sensitive toward antibiotic imipenem.